Farnesoid-X receptor as a therapeutic target for inflammatory bowel disease and colorectal cancer - Zhou, Mengjiao; Wang, Danfeng; Li, Xiang; Cao, Ying; Yi, Chengxue; Wiredu Ocansey, Dickson Kofi; Zhou, Yuling; Mao, Fei (Frontiers in Pharmacology, 2022)
Farnesoid-X receptor (FXR), as a nuclear receptor activated by bile acids, is a vital molecule involved in bile acid metabolism. Due to its expression in immune cells, FXR has a significant effect on the function of immune cells and the release of chemokines when immune cells sense changes in bile acids. In addition to its regulation by ligands, FXR is also controlled by post-translational modification (PTM) activities such as acetylation, SUMOylation, and methylation. Due to the high expression of FXR in the liver and intestine, it significantly influences intestinal homeostasis under the action of enterohepatic circulation. Thus, FXR protects the intestinal barrier, resists bacterial infection, reduces oxidative stress, inhibits inflammatory reactions, and also acts as a tumor suppressor to impair the multiplication and invasion of tumor cells. These potentials provide new perspectives on the treatment of intestinal conditions, including inflammatory bowel disease (IBD) and its associated colorectal cancer (CRC). Moreover, FXR agonists on the market have certain organizational heterogeneity and may be used in combination with other drugs to achieve a greater therapeutic effect. This review summarizes current data on the role of FXR in bile acid metabolism, regulation of immune cells, and effects of the PTM of FXR. The functions of FXR in intestinal homeostasis and potential application in the treatment of IBD and CRC are discussed.